TRANSPORT OF GOODS ON THE EXAMPLE OF A SELECTED SECTION OF TRANSPORT IN POLAND - Elżbieta MACIOSZEK; Irena JURDANA (Scientific Journal of Silesian University of Technology. Series Transport)
The article presents the issue of the transport of goods in relation to sea transport. Sea transport has been known to mankind for a long time. Currently, maritime transport is not limited only to the transport of goods and/or passengers along sea routes, which are carried out between seaports using appropriately adapted means of transport. It is a branch of transport, which consists of a very good knowledge of navigation, highly specialized staff, and a wide range of containers for transporting various types of cargo, often requiring specialized conditions. In addition, sea transport is perfectly combined with intermodal transport, so that in the end, the transport process is the most beneficial for all participants, i.e., the customers, sellers, distributors, and manufacturers. The main purpose of the article was to present the volume of goods transported in this branch of transport. The article, after introducing the issue, presents the classification of sea vessels, refers to the market of maritime transport services and its conditions for further development, and analyzes the overall volume of goods transported in the seaports of Gdańsk and Gdynia against the background of other Polish seaports in the years 2011-2021.